Tea Plantation in Tourism, Conservation, and Economic Perspectives (a Study on Pagilaran Tea Plantation, Batang Regency)‎ - Raras Gistha Rosardi; Sucihatiningsih Dian Wisika Prajanti; Hamdan Tri Atmaja; Juhadi Juhadi (Universitas Negeri Semarang, 2021)
The plantation sector is a conflict-prone sector. The interests of various parties are disembogued in the plantation sector. Policies, legal regulations, hopes to provide welfare and a vehicle for research and education are part of the dynamics of Plantation. The objectives of this research is to findings in the form of a new perspective on Pagilaran tea plantations. The method used in this research is qualitative. Tea plantation is the leading sector in Indonesia which is favored by beautiful natural scenery, superior tea commodities, and efforts to preserve nature. Pagilaran Tea Plantation has core businesses in the form of Production, Trade, and Agrotourism. Pagilaran tea plantation is an icon of family-based tourism and study tour. Pagilaran develops its plantations in accordance with RA (Rainforest Alliance) standards and government regulations. PT Pagilaran is also committed to always playing an active role in preserving the environment. Tour packages based on the potential of natural resources and education of tea commodities become the main attraction for Pagilaran, including Tea Walking, Tea Factory, and Sun Rise at Tea Plantation Peak‎. The management principle of PT. Pagilaran Tea Plantation is a Closed Cluster Economy that empowers local communities to be empowered in Pagilaran Tea Plantation‎.